Encounter with Covid 19: A Personal Experience! - Iram, Mahvash (Indian Journal of Pharmacy Practice)
The paranoia surrounding COVID-19 is I would say overrated! The fight against this noxious virus can be conquered with judicious decisions and appropriate measures. At first it felt like any another day where I am overworked leading to fatigue which turned out to be myalgia and severe headache by end of the day. As a routine, popped in a paracetamol (Dolo 650) which gave me relief after an hour. On day 2, I was asymptomatic except for headache, although there was a feeling of fever from within and the thermometer just showed reading of 99°F. Since there was vulnerable group in the vicinity, I decided to self-quarantine and in order to rule out any ambiguity, I provided the sample for COVID-19 testing. Next morning, worst of my nightmares came true when the RT-PCR report showed positive for COVID-19 E gene and COVID-19 RdRP gene. The immediate step was to ensure that my family is protected and hence got them all tested and mercifully the virus had spared them all.